The Development of Models of Learning Basic Motoric Skills in Sports for Deaf Children - Anggri Dwi Nata; Hilda Oktri Yeni; Wiwik Yunitaningrum; Edi Kurniawan; Karunia Yulinda Khairiyah; Fitria Meilina; Hermawan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The problem in this study is that there is no varied learning model in sports learning, especially to improve the motor skills of deaf students. This study aims to create a basic movement learning model for sports motor skills in deaf students. This study uses the ADDIE method, in ADDIE research 5 stages namely analysis, design, model development, implementation, and evaluation. The analysis technique used is descriptive analysis. The results of the study are: a) The development of a basic motion learning model for sports motor skills in deaf students is feasible and can be used. b) The product of basic motion learning models for sports motor skills for deaf students has been tested and proven to improve the motor skills of deaf children. The development of basic movement learning models for sports skills for deaf students has a 100% ease of implementation, 86.3% clarity of implementation, 100% interest, 81.8% safety in implementation and 86.3% of equipment used.